On technique for counting of fish pyloric appendages - Anna E. Lapshina (Известия ТИНРО)
New technique for collecting, fixing and counting of fish pyloric appendages is described that does not use any chemical fixing reagent. It includes storing of chemically untreated deep-frozen samples during unlimited time, defrosting the samples, and heat treatment the samples in microwave oven depending on weight of sample and power of the oven. The technique allows to avoid work with toxic reagents, as ethanol and formalin, and to lower the costs of investigation.